Severe Cutaneous Adverse Reactions Associated With High-Dose Lamotrigine for Mood Disorders: A Case Series - Abigale Clark; Blake St. Clair (University of Minnesota Libraries Publishing, 2022)
Drug-induced Eosinophilia and Systemic Symptoms (DRESS), Stevens-Johnson Syndrome (SJS), and Toxic Epidermal Necrolysis (TEN) are rare but life-threatening immune-mediated drug reactions known as Severe Cutaneous Adverse Reactions (SCARs). These severe drug reactions have been associated with many commonly prescribed medications, including sulfonamides, allopurinol, carbamazepine, and several antiepileptic drugs including lamotrigine.1 Although the risk of these adverse events is recognized by many medical providers, the risk may be overlooked when prescribing lamotrigine for mood disorders.  Review of the literature and the experience of these cases suggest that the risk of lamotrigine-associated SCARs is increased when starting lamotrigine at high initial doses. Here we present and discuss two cases of SCARs attributed to high-dose lamotrigine prescribed for mood disorders. A third patient also presented with a SCAR related to high-dose lamotrigine prescribed for a mood disorder during this time but was lost to follow-up and was not reachable. All three patients presented to our hospital system from 2019-2020. Due to this clinical experience, we recommend that pharmacists and prescribers alike be alerted of the risk of severe cutaneous drug reactions when lamotrigine is prescribed, particularly at initial doses greater than 25 mg.